Asymmetric cyanine as a far-red fluorescence probe for mitochondrial viscosity - Park, Sang Jun; Shin, Bong Ki; Lee, Hyo Won; Song, Ju Man; Je, Jong Tae; Kim, Hwan Myung (Dyes and Pigments, 2020)
Mitochondrial viscosity affects respiratory state and signal transduction. As a result, abnormal mitochondrial viscosity leads to diabetes, accelerated aging, insulin resistance, Alzheimer's disease, Parkinson's disease, and Huntington's disease. Previously reported probes for mitochondrial viscosity have absorption and emission wavelengths in the green to orange region and thus are hampered by interference with biomolecules. In addition, rotors with disubstituted double bonds have low photostability, due to photoisomerization. Here, we report a new far-red viscosity probe, SFC-Cy007, which has high photostability, due to a tetrasubstituted double bond. This probe was selectively located in the intracellular mitochondria and immediately responded to changes in mitochondrial viscosity via swelling and inflammatory responses. Furthermore, SFC-Cy007 stained well at very low concentrations in the hippocampal tissue, allowing visual observation of viscosity distribution in hippocampal tissue for the first time.
Keywords: Absorption and emissions; Alzheimer's disease; Asymmetric cyanine; Huntington's disease; Inflammatory response; Molecular rotors; Red fluorescence; Viscosity distribution; Asymmetric cyanine; Far-red fluorescence probe; Mitochondrial viscosity; Molecular rotor